Atrial fibrillation is associated with decreased total cerebral blood flow and brain perfusion - Gardarsdottir, Marianna; Sigurdsson, Sigurdur; Aspelund, Thor; Rokita, Hrafnhildur; Launer, Lenore J; Gudnason, Vilmundur; Arnar, David O (Europace (London, England), 2018)
Abstract Aims Atrial fibrillation (AF) has been associated with cognitive impairment. Additionally, brain volume may be reduced in individuals with AF. Potential causes may include cerebral micro-embolism or reduced stroke volume due to the beat-to-beat variation in AF. The aims of this study were to measure cerebral blood flow and estimate whole brain perfusion in elderly individuals with and without AF. Methods and results Blood flow in the cervical arteries was measured with phase contrast MRI and brain perfusion estimated in a large cohort from the AGES-Reykjavik Study. Individuals were divided into three groups at the time of the MRI: persistent AF, paroxysmal AF, and no history of AF. Of 2291 participants (mean age 79.5 years), 117 had persistent AF and 78 had paroxysmal AF but were in sinus rhythm at the time of imaging AF. Those with persistent AF had lower cholesterol and used more anti-hypertensive medication and warfarin. The three groups were similar with regard to other cardiovascular risk factors. Those in the persistent AF group had significantly lower total cerebral blood flow on average, 472.1 mL/min, both when compared with the paroxysmal AF group, 512.3 mL/min (P < 0.05) and the no AF group, 541.0 mL/min (P < 0.001). Brain perfusion was lowest in the persistent AF group, 46.4 mL/100 g/min compared with the paroxysmal AF group, 50.9 mL/100 g/min in (P < 0.05) and those with no AF, 52.8 mL/100 g/min (P < 0.001). Conclusion Persistent AF decreases blood flow to the brain as well as perfusion of brain tissue compared with sinus rhythm.